Total marrow irradiation (TMI): Addressing an unmet need in hematopoietic cell transplantation - a single institution experience review - Wong, Jeffrey Y.C.; Liu, An; Han, Chunhui; Dandapani, Savita; Schultheiss, Timothy; Palmer, Joycelynne; Yang, Dongyun; Somlo, George; Salhotra, Amandeep; Hui, Susanta; Al Malki, Monzr M.; Rosenthal, Joseph; et al. (Frontiers in Oncology, 2022)
Purpose TMI utilizes IMRT to deliver organ sparing targeted radiotherapy in patients undergoing hematopoietic cell transplantation (HCT). TMI addresses an unmet need, specifically patients with refractory or relapsed (R/R) hematologic malignancies who have poor outcomes with standard HCT regimens and where attempts to improve outcomes by adding or dose escalating TBI are not possible due to increased toxicities. Over 500 patients have received TMI at this center. This review summarizes this experience including planning and delivery, clinical results, and future directions. Methods Patients were treated on prospective allogeneic HCT trials using helical tomographic or VMAT IMRT delivery. Target structures included the bone/marrow only (TMI), or the addition of lymph nodes, and spleen (total marrow and lymphoid irradiation, TMLI). Total dose ranged from 12 to 20 Gy at 1.5-2.0 Gy fractions twice daily. Results Trials demonstrate engraftment in all patients, and a low incidence of radiation related toxicities and extramedullary relapses. In R/R acute leukemia TMLI 20 Gy, etoposide, and cyclophosphamide (Cy) results in a 1-year non-relapse mortality (NRM) rate of 6% and 2-year overall survival (OS) of 48%; TMLI 12 Gy added to fludarabine (flu) and melphalan (mel) in older patients (> 60 years old) results in a NRM rate of 33% comparable to flu/mel alone, and 5-year OS of 42%; and TMLI 20 Gy/flu/Cy and post-transplant Cy (PTCy) in haplo-identical HCT results in a 2-year NRM rate of 13% and 1-year OS of 83%. In AML in complete remission, TMLI 20 Gy and PTCy results in 2-year NRM, OS, and GVHD free/relapse-free survival (GRFS) rates of 0%, 86·7%, and 59.3%, respectively. Conclusion TMI/TMLI shows significant promise and low NRM rates, the ability to offer myeloablative radiation containing regimens to older patients, the ability to dose escalate, and response and survival rates that compare favorably to published results. Collaboration between radiation oncology and hematology is key to successful implementation. TMI/TMLI represents a paradigm shift from TBI towards novel strategies to integrate a safer and more effective target-specific radiation therapy into HCT conditioning beyond what is possible with TBI and will help redefine and expand the role of radiotherapy in HCT.